2023
DOI: 10.3390/buildings13071865
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Varying Fiber Dosages as Stirrup Substitutes in Torsion-Loaded Concrete Beams

Abstract: Over the past few decades, numerous studies have explored the use of steel fiber (SF) as an alternative to transverse reinforcement rebars in reinforced concrete beams, either partially or completely replacing them. However, there are limited studies that have investigated the effect of fiber dosage and length on reinforced concrete beam performance under torsional loads without the use of transverse reinforcement rebars. In this study, experimental investigations were conducted to examine the performance of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This phenomenon was attributed to the absence of stirrups in these areas, which led to a weak overall tensile capacity. The uneven terrain at the testing site further contributed to this cracking [ 19 ].…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…This phenomenon was attributed to the absence of stirrups in these areas, which led to a weak overall tensile capacity. The uneven terrain at the testing site further contributed to this cracking [ 19 ].…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…Muna et al found that steel fibers have a significant impact on the flexural, tensile, and compressive strength of concrete beams according to investigations into the torsional performance of beams reinforced with different volumes of steel fiber. Furthermore, a volume content of 1.0% steel fibers can fully compensate for the decreased torsional strength in beams due to the absence of stirrups [23]. The advantages of this newly developed concrete have already been identified by many civil engineers and researchers [18,19,24].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, shear or torsional strength cannot be significantly improved with high-strength bars alone. SFRC mainly increases shear and torsional capacity and the cracking moment of elements [6][7][8]23]. These materials can increase the overall performance of members, including the different aspects mentioned above, if jointly employed in concrete beams under complex loadings.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a comprehensive assessment of the seismic behavior of reinforced concrete structures, this study specifically focuses on the effect of two different types of stirrups, i.e., hooked and unhooked stirrups. Previous research has shown that hooked stirrups can improve energy dissipation and ductility by providing additional restraint to the concrete core, while unhooked stirrups, although widely used, may provide relatively limited benefits in this regard [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Rosso et al [19] estimated the effect of corrosion on the capacity and ductility in their study.…”
Section: Introductionmentioning
confidence: 99%